Answer:
a) Cr2(SO4)3(aq) + 3(NH4)2CO3(aq) → Cr2(CO3)3(s) + 3(NH4)2SO4(aq)
b) Ba(NO3)2(aq) + K2SO4(aq) → BaSO4(s) + 2KNO3(aq)
c) Fe(NO3)2(aq) + 2KOH(aq) → Fe(OH)2(s) + 2KNO3(aq)
Step-by-step explanation:
a. Cr2(SO4)3(aq) + (NH4)2CO3(aq)
Cr2(SO4)3(aq) + 3(NH4)2CO3(aq) → 2Cr^3+ + 3SO4^2- + 6NH4+ + 3CO3^2-
2Cr^3+ + 3SO4^2- + 6NH4+ + 3CO3^2- → Cr2(CO3)3 + 3(NH4)2SO4
Cr2(SO4)3(aq) + 3(NH4)2CO3(aq) → Cr2(CO3)3(s) + 3(NH4)2SO4(aq)
b. Ba(NO3)2(aq) + K2SO4(aq)
Ba(NO3)2(aq) + K2SO4(aq) → Ba2+ +2NO3- + 2K+ + SO4^2-
Ba2+ +2NO3- + 2K+ + SO4^2- → BaSO4 + 2KNO3
Ba(NO3)2(aq) + K2SO4(aq) → BaSO4(s) + 2KNO3(aq)
c. Fe(NO3)2(aq) + KOH(aq)
Fe(NO3)2(aq) + 2KOH(aq) → Fe^2+ + 2NO3- + 2K+ + 2OH-
Fe^2+ + 2NO3- + K+ + OH- → Fe(OH)2 + 2KNO3
Fe(NO3)2(aq) + 2KOH(aq) → Fe(OH)2(s) + 2KNO3(aq)